Pelatihan Wawancara Kerja dalam Bahasa Inggris bagi Siswa-Siswi Kelas XI SMK Dharma Bakti 4 Jambi - Paskalina Widiastuti Ratnaningsih (Jurnal Pengabdian Masyarakat PGSD, 2021)
The aim of this community service is for vocational high school students to be able to speak English fluently in a job interview. Vocational high school students are prepared to be able to work directly after graduating so that job interview training is needed to prepare the students in the working area. Besides using Indonesian, job interview uses English in this era. Hence, the ability to a job interview in English is needed. The method in community service is by giving job interview training in English to students. There are two results in this community service. The first is training activity is started with several steps until the students can practice job interviews in English. The second is a job interview in English is beneficial for the students. The students are able to know the vocabulary and practice pronouncing it well for a job interview in English. The students are able to speak in English for a job interview. This community service training is important for preparing vocational high school students to work.